Interaction between fiscal and monetary policy in a dynamic nonlinear model - Bertella, Mario A. [UNESP]; Rego, Henio A.; Neris, Celso; Silva, Jonathas N. [UNESP]; Podobnik, Boris; Stanley, H. Eugene (Public Library Science, 2015)
The objective of this study is to verify the dynamics between fiscal policy, measured by public debt, and monetary policy, measured by a reaction function of a central bank. Changes in monetary policies due to deviations from their targets always generate fiscal impacts. We examine two policy reaction functions: the first related to inflation targets and the second related to economic growth targets. We find that the condition for stable equilibrium is more restrictive in the first case than in the second. We then apply our simulation model to Brazil and United Kingdom and find that the equilibrium is unstable in the Brazilian case but stable in the UK case.